Embeddedness and growth of small businesses in rural regions. (August 2018) - Greenberg, Zeevik; Farja, Yanay; Gimmon, Eli
Abstract: This paper explores the development of local small businesses in rural peripheral regions compared to businesses in urban settings, and the impact of the local business' location and level of embeddedness on its growth, measured by the number of employees. The study was conducted using a mixed-method sequential methodology, with a quantitative survey of 613 small rural and urban businesses in Israel, followed by 13 in-depth interviews with rural entrepreneurs who were selected from the quantitative sample. This study found an advantage of double-layered network embeddedness employed by rural business owners, i.e. both local and outside of the region, for the growth of small and medium sized enterprises (SMEs). The contribution of this study is expansion of the concept of extra-local embeddedness to enhance growth of SMEs in rural-peripheral regions. The main theoretical contribution of this paper is the description of double-layered network embeddedness employed by rural business owners, who are embedded in local and regional networks, alongside extra-regional and national (extra-local) networks, in an attempt to overcome some of the distance-related obstacles of their location. Furthermore, our findings suggest that this type of embeddedness, as well as the embeddedness of family members in small businesses, can enhance the growth potential of the local businesses, as does the location of the business in the owner's home or in its close proximity. We propose a spatial model of the embeddedness of small rural businesses at various levels of proximity. Highlights: We explore the development of small businesses in rural regions with a mixed-methods design. Embeddedness in extra-regional networks has a significant effect on business growth. In-depth interviews explain the characteristics of extra-regional embeddedness and its importance to SMEs. We propose a hierarchical-spatial model of SME embeddedness and its contribution to growth.